Upaya Pencegahan Penyakit Jembrana pada Sapi Bali Melalui Edukasi bagi Kelompok Peternak Sumber Rejeki di Desa Alebo, Kecamatan Konda, Kabupaten Konawe Selatan - Fadli Ma’mun Pancar; Rahman Rahman; Syamsuddin Syamsuddin; Nurhayu Nurhayu; Mansyur Mansyur; Awal Maulid Sari; Nisfu Sakban; Saniwanti Saniwanti (Indo Publishing, 2026)
Jembrana disease is one of the important infectious diseases affecting bali cattle and may cause economic losses for farmers due to decreased productivity, treatment costs, and livestock mortality. Farmers’ limited knowledge of clinical symptoms, transmission routes, risk factors, and preventive measures remains one of the challenges in controlling this disease at the smallholder farming level. This community service activity aimed to improve farmers’ knowledge and awareness of Jembrana disease in Bali cattle in Alebo Village, Konda District, South Konawe Regency. The activity was conducted on November 24, 2025, at the Alebo Village Hall and involved 40 participants, consisting of the village head, village officials, and members of the Sumber Rejeki Livestock Farmers Group. The method used in this activity included direct education, discussion, question-and-answer sessions, and evaluation of participants’ understanding. The materials delivered covered an introduction to Jembrana disease, clinical symptoms, transmission routes, risk factors, barn biosecurity, vektor control, quarantine of newly introduced cattle, case reporting, and the importance of vaccination. The results showed that participants were enthusiastic in attending the activity and gained a better understanding of Jembrana disease prevention. This educational activity encouraged farmers to independently implement preventive measures, such as maintaining barn hygiene, controlling blood-sucking insects, separating sick animals, and coordinating with animal health officers. Therefore, this educational activity plays an important role in improving farmers’ capacity to prevent the spread of Jembrana disease in Bali cattle.